Determination of Phytochemicals and Antioxidants Activity in Herbs Spices of Kitchen - Botahala, Loth; Djasibani, Hemy R.; Kafolamau, Sua F.; Likma, Yubelinda (Journal of Science and Technology, 2024)
Maintaining immunity is important because it can prevent infection of various viruses. One way to maintain immunity is by consuming herbal plants. The properties and benefits of several herbal plants that are often used as kitchen spices have been explained scientifically in the book Herbal Spices for Kitchen. In Alor Regency, East Nusa Tenggara Province, Indonesia, turmeric, which is rich in curcumin, is usually used as a wound medicine by rural communities. Likewise, ginger, which has a spicy taste, is often used by rural communities to warm cold babies by occasionally placing it on the baby's armpit. Meanwhile, lemongrass is usually used to add flavor to dishes at parties. Based on consideration of the local community's experience in using these three plants and combined with scientific studies, it was deemed necessary to analyze the content of phenolic compounds, saponins, steroids, terpenoids, and alkaloids, as well as antioxidant activity in a mixture of turmeric, ginger, and lemongrass with the ratio of 50% turmeric, 33.33% ginger, 16.67% lemongrass. The distribution of phenolic compounds, saponins, steroids, terpenoids, and alkaloids, even in the mixture of turmeric, ginger, and lemongrass plants is very strong antioxidant activity as indicated by the  value of the mixture of 4.817 ?g/ml. The composition of the mixture of turmeric, ginger, and lemongrass can contribute to maintaining and even strengthening the body's immune system.